SOME NEW OSTROWSKI TYPE INEQUALITIES FOR GENERALIZED (s, m, ϕ)-PREINVEX FUNCTIONS VIA FRACTIONAL INTEGRAL OPERATORS - Kashuri, Artion; Liko, Rozana (Matematichki Bilten, 2017)
In the present paper, the notion of generalized \((s, m, φ)\)-preinvex function is applied to establish some new generalizations of Ostrowski type inequalities via fractional integral operators. These results not only extend the results appeared in the literature (see [1]) but also provide new estimates on these type. Some applications to special means are also given.